Combining ability of new pistillate lines for plant growth attributes, seed yield and its components in castor (Ricinus communis L.): COMBINING ABILITY OF PISTILLATE LINES OF CASTOR FOR GROWTH, YIELD AND YIELD COMPONENTS - C LAVANYA; T MANJUNATH; K T RAMYA (Journal of Oilseeds Research, 2018)
Combining ability of four newly developed pistillate lines were tested using Line x Tester analysis. Sixteen hybrids generated using four pistillate lines and four testers were studied along with parents and three checks to estimate combining ability for nine characters in castor. Non-additive gene action was preponderant in all the characters studied except for seed yield, which indicated a negative estimate. Among the female parents, IPC-15 (DPC-15) was a good general combiner for earliness and short plant height while IPC-19 (IPC-19) for late duration and tall plant height. Three pistillate lines, DPC-15 (IPC-15), DPC-19 (IPC-19) and DPC-21 (IPC-21) were identified as good general combiners for total and effective primary spike length. Among the eight parents studied, DCS-107 was a good general combiner for seed yield and other traits like total primary spike length, effective primary spike length and 100-seed weight. None of the hybrids were good specific combiners for seed yield and several other yield contributing characters while three hybrids viz., DPC-16 x DCS-107 (1800 kg/ha), DPC-15 x DCS-107 (1646 kg/ha) and DPC-21 x DCS-107 (1595 kg/ha) were identified as the top three performing hybrids. Among them, DPC-21 x DCS-107 (DCH-1720), has been tested in the All India Coordinated multi location trials for three years while DPC-15 x DCS-107 (PHT-12-2) wastested in three locations (2014-15) and found promising.